The effect of dietary patterns on risk factors for CHD : a comparative study of students residing at the Adventist International Institute of Advanced Studies in the Philippines - Jenneke, Cindy A. N. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2006.